Molecular docking of taraxerol acetate as a new COX inhibitor (Bangladesh Journal of Pharmacology, 2013)
Cycloxygenase inhibitors are one of the main class of therapeutic agents for management of inflammation. New COX inhibitors are discovered from natural and synthetic sources. In the current investigation taraxerol acetate have been discovered as a new COX inhibitor. Taraxerol acetate showed considerable inhibitory activity against both COX-1 (IC50: 116.3 ± 0.03 ?M) and COX-2 (IC50: 94.7 ± 0.02 ?M) enzymes using in-vitro enzyme inhibition assay. Molecular docking revealed significant interactions of taraxerol acetate with the important amino acid residues surrounding the inhibitor in binding pocket of COX-2 enzyme. This study indicate potential of taraxerol acetate to be further explored and modified as a new lead compound for better management of inflammatory conditions via targeting COX enzymes.